 # Linear Equations in One Variable

63. The shifting of a number from one side of an equation to other is called

• (A) Transposition
• (B) Distributivity
• (C) Commutativity
• (D) Associativity

62. A term of an equation can be transposed to the other side by changing

• (A) Its value
• (B) Its sign
• (C) Power of the variable
• (D) None of these

61. Linear equation in one variable has

• (A) Only one variable with any power
• (B) Only one term with a variable
• (C) Only one variable with power 1
• (D) Only constant term

60. A linear equation in one variable has

• (A) Only one solution
• (B) Two solutions
• (C) More than two solutions
• (D) No solution

59. Which of the following is a linear expression?

• (A) x2 + 1
• (B) y + y2
• (C) 4
• (D) 1 + z

58. If a and b are positive integers, then the solution of the equation ax = b has to be always

• (A) Positive
• (B) Negative
• (C) One
• (D) Zero

57. If x = a, then which of the following is not always true for an integer k?

• (A) kx = ak
• (B) x/k = a/k
• (C) x k = a k
• (D) x + k = a + k

56. In the equation 3x – 3 = 9, transposing –3 to RHS, we get

• (A) 3x = 9 – 3
• (B) 3x = – 9 + 3
• (C) 3x = 9 + 3
• (D) – 3x = 9 + 3

55. If 9 is added to a number, it becomes 25. This statement in the form of an equation is

• (A) x + 9 = 25
• (B) x – 9 = 25
• (C) 9x = 25
• (D) x/9 = 25

54. In the equation 2x = 4 – x, transposing –x to LHS, we get

• (A) x = 4
• (B) 2x = 4
• (C) 3x = 4
• (D) –x = 4

53. The solution of the equation ax + b = 0 is

• (A) x = a/b
• (B) x = b/a
• (C) x = −a/b
• (D) x = −b/a

52. The value of x for which the expressions 3x – 4 and 2x + 1 become equal is

• (A) –3
• (B) 0
• (C) 5
• (D) 1

51. The value of z when z/1.2 = 1.5 is

• (A) z = 18
• (B) z = 0.18
• (C) z = 1.8
• (D) z = 1.08

50. The solution of the equation 3x – 4 = 1 – 2x is

• (A) 4/5
• (B) 1/15
• (C) 10
• (D) 0

49. The solution of which of the following equations is neither a fraction nor an integer.

• (A) 3x + 2 = 5x + 2
• (B) 4x – 18 = 2
• (C) 4x + 7 = x + 2
• (D) 5x – 8 = x + 4

48. The statement adding 15 to 4 times x is 39, when converted to an equation becomes

• (A) 4x + 15 = 39
• (B) 15x + 4 = 39
• (C) 4x – 15 = 39
• (D) 4x + 15 + 39 = 0